Two new species of Conognatha Eschscholtz, 1829 (Coleoptera, Buprestidae, Stigmoderini) from Southeast and South Brazilian regions with distributional notes - Portela, Clayton; Mermudes, José Ricardo M. (Zootaxa, 2014)
Conognatha (Pithiscus) coffeatus sp. nov. and Conognatha (Pithiscus) puris sp. nov., both from the Atlantic Rainforest (type locality: Itatiaia, Rio de Janeiro State, Brazil), are described and illustrated. They differ from each other mainly by the elytral colour pattern, presence of a short longitudinal groove between the vertex and the frons in C. (P.) puris sp. nov., and differences in frons shape, antennae sensory fields, pronotum and aedeagus. The distribution of C. (P.) gounellei is extended to the State of Minas Gerais, Brazil. A modified key to include the new species, as well as illustrations, are presented.